2007
DOI: 10.1037/0021-843x.116.1.116
|View full text |Cite
|
Sign up to set email alerts
|

Major life events and major chronic difficulties are differentially associated with history of major depressive episodes.

Abstract: Major life events have been found to precede onsets of a 1st lifetime episode of depression more commonly than subsequent recurrences. Despite general empirical support for this finding, few data directly address how the role of major life events may change over successive recurrences. Further, little research has examined major chronic difficulties in relation to a 1st lifetime episode versus a recurrence of depression. The present study tested the associations between major life events and major difficulties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 23 publications
6
79
2
2
Order By: Relevance
“…Research on major life stressors has revealed that chronic, persistent life difficulties play a significant role in the onset and recurrence of depressive episodes (Hammen, 2005;Monroe, Slavich, Torres, & Gotlib, 2007). Given that racial microaggressions contribute to perceived stress, African-Americans have the added burden of managing these race-related events, which ultimately puts them at greater risk for experiencing depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Research on major life stressors has revealed that chronic, persistent life difficulties play a significant role in the onset and recurrence of depressive episodes (Hammen, 2005;Monroe, Slavich, Torres, & Gotlib, 2007). Given that racial microaggressions contribute to perceived stress, African-Americans have the added burden of managing these race-related events, which ultimately puts them at greater risk for experiencing depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, the one study that has specifically examined occurrence produced findings consistent with the present ones. Monroe et al, (2007) found that SLEs were less likely to be present prior to depressive episodes as the episode number increased. Although the authors did not examine the impact of SLEs, they predicted that SLEs retained their capacity to trigger MDEs but were less likely to be present prior to recurrences.…”
Section: Occurrence and Impact Of Sles As A Function Of History Of Dementioning
confidence: 94%
“…Although our hypotheses focused on acute life events, onset and severity of depression are also known to be influenced by levels of recent chronic stress (Hammen, 2005; Monroe et al, 2007, 2009). Consequently, we also assessed participants’ levels of chronic stress burden and impact over the past six months in several key domains (i.e., close friendships, social life, romantic relationships, family relations, work, school, finances, and the health of the participant and his or her family) and controlled for these levels in all analyses.…”
Section: Methodsmentioning
confidence: 99%